Charting the future of PLOS Medicine: priorities for evidence, impact, and equity - Lumbard, Helen; Bärnighausen, Till (PLoS medicine, 2025)
As PLOS Medicine enters a new chapter, its leadership sets out a bold editorial vision grounded in evidence, impact and equity. In a rapidly evolving global health landscape, the journal reaffirms its commitment to diversity, openness, and actionable science, ensuring research not only reflects the world’s needs, but drives meaningful change.